Doktora Atkinsa kolejna nowa rewolucyjna dieta - Atkins, Robert C. (Warszawa : Amber, 2003)
Polish translation of "Dr. Atkins' new diet revolution". A guide to the well known low-carbohydrate weight reducing diet.
Keywords: Reducing diets; Low-carbohydrate diet